PENGEMBANGAN GAME EDUKASI PIXEL ADVENTURE “TANTANGAN MASTERMIND MATEMATIKA: THE QUEST FOR NUMERIA” SEBAGAI ALAT BANTU PEMBELAJARAN MATEMATIKA DI KELAS X - Farhan; Nurmayanti; Madaling (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics lessons often have difficulty in motivating students and making them understand the concepts taught. One creative way to use it is through the use of educational games. The focus of this research is to create an educational game in Unity3D to teach mathematics to class X students. The game